Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Their own agenda: The history, development, and culture of women's orchestras outside the united states - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; approches et analyses; arts; discipline; femmes* musiciennes; genre; histoire des femmes*; histoire et politique; inégalités; musique; mémoires/thèses; périodes historiques; ressource en ligne; systèmes d'oppressions; thématiques

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

Les représentations médiatiques des femmes aux élections municipales et la politique vue par les journaux étudiants universitaires québécois: des représentations genrées et équilibrées - Bourassa-Dansereau, Caterine; Lalancette, Mireille; Morin, Laurence; Rouillard, Carol-Anne; Table de concertation des groupes de femmes de la Montérégie; Théberge-Guyon, Marianne (Service aux collectivités de l'UQAM/Table de concertation des groupes de femmes du Bas St-Laurent/Tables de concertation des groupes de femmes de la Montérégie/Table de concertation du mouvement des femmes de la Mauricie, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; citoyenneté; femmes*; histoire et politique; politique; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; thématiques

Le racisme est un problème de blancs - Eddo-Lodge, Reni; Mazoyer, Renaud (Éditions Autrement, 2018)
« Quand des Blancs feuillettent un magazine, surfent sur Internet ou zappent à la télévision, il ne leur semble jamais étrange de voir des gens qui leur ressemblent en position d'autorité. Les affirmations positives de la blanchité sont tellement répandues que le Blanc moyen ne les remarque même pas. Etre blanc, c'est être humain ; être blanc, c'est universel. Je ne le sais que trop, car je ne suis pas blanche." Après l'élection de Barack Obama, certains ont proclamé l'avènement d'une société post-raciale. Avec une liberté de ton décapante, Reni Eddo-Lodge montre ici combien nous en sommes loin. Elle analyse les méfaits d'un racisme structurel persistant d'autant plus sournois qu'il avance masqué. Car le racisme va bien au-delà de la discrimination ou de l'injure personnelle. Il imprègne le récit historique, l'imaginaire collectif, les institutions et les entreprises. Pourquoi les Blancs pensent-ils ne pas avoir d'identité raciale? Pourquoi la simple idée d'un James Bond noir fait-elle scandale? Comment une fillette noire en vient-elle à se persuader qu'en grandissant, elle deviendra blanche? Le racisme n'est pas une question de valeur morale, mais d'exercice du pouvoir. Entretenir la légende d'une égalité universelle n'aide en rien. Au contraire. Car, pour déconstruire le racisme, il faut commencer par reconnaître l'étendue du privilège blanc. »-- 4ème de couverture.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afro-féminisme; approches et analyses; com5170; communication; cours; discipline; europe; féminisme afropéen; histoire et politique; journalisme; premier cycle; privilèges; périodes historiques; racisme; racisme systémique; représentation des femmes* racisées; royaume-uni; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Lutter contre les violences conjugales : féminisme, travail social, politique publique - Herman, Elisa; Lagrave, Rose-Marie (Le sens social, 2018)
Comprendre les violences faites aux femmes dans le couple c'est aussi analyser les luttes, les politiques publiques et les actions concrètes déployées en France aujourd'hui. Ce livre prend appui sur une enquête ethnographique menée auprès d'associations spécialisées (souvent membres de la Fédération nationale solidarité femmes), de femmes victimes, de professionnels de nombreuses institutions concernées (justice, police, travail social...) et de personnalités politiques et universitaires actifs sur ces sujets. S'adressant aux universitaires ainsi qu'aux professionnels, l'ouvrage décrit la construction de la cause des violences conjugales, ainsi que les politiques publiques mises en œuvre, dans une démarche sociohistorique. Il met ainsi en lumière la porosité des espaces militant, universitaire et institutionnel. L'analyse des carrières militantes et professionnelles, la prise en compte des parcours des femmes rencontrées et du contexte du nouveau management public structurant l'action publique, enrichissent la compréhension du travail social féministe mis en œuvre dans les structures d'accueil et d'hébergement des femmes victimes de violences conjugales et de leurs enfants. Cette recherche sociologique éclaire alors des engagements féministes professionnels trop peu connus, face au paradoxe d'un intérêt politique fort pour lutter contre des violences masculines toujours persistantes.
Keywords: 2000 à aujourd'hui; 2010-2019; cours; cycles supérieurs; discipline; fem7000; histoire et politique; périodes historiques; sciences humaines; thématiques; travail social; violences; violences conjugales

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap